Perception of pain and its control: all that we don't know yet - Mario Tiengo (Publiediting, 2008)
Neurophysiology of pain is comprehensible (at least within certain levels) until events related to classic physics are concerned. In order to face the topic of the perception of the pain we have to analyze the mental factors like the suggestion (placebo), the emotional events and the tone of humor. The perception of the pain can be explored in the world of quanti.